Barriers to and facilitators of implementing obstructive sleep apnea screening in stroke patients: a scoping review protocol - Lin, Yashi; Zhao, Jiali; Xiao, Wenhui; Ding, Fang; Fang, Zhen; Guo, Liang; Lou, Shuhui (Frontiers in Neurology, 2025)
IntroductionObstructive sleep apnea (OSA) is a highly prevalent but frequently undiagnosed sleep disorder among stroke patients. It is associated with increased risks of stroke recurrence, reduced rehabilitation effectiveness, and elevated mortality. Despite guideline recommendations for routine OSA screening in stroke care, implementation remains inconsistent in clinical practice. As a modifiable sleep-related risk factor with significant implications for neurological outcomes, better integration of OSA screening in post-stroke care is urgently needed. Thus, this scoping review protocol outlines a systematic approach to identifying barriers to and facilitators of OSA screening in stroke populations.Methods and analysisThis scoping review will follow the methodological framework provided by the Joanna Briggs Institute (JBI) and will be reported using Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) guidelines. The search will be performed on CNKI, WanFang, SinoMed, PubMed, Embase, Web of Science, the Cochrane Library, CINAHL, ProQuest Dissertations, OpenGrey, and Google Scholar. Targeted searches of international organization websites will also be conducted. No restrictions will be imposed based on study design or year of publication. Data will be synthesized using the content analysis approach and mapped onto the Ottawa Model of Research Use (OMRU), including domains such as evidence-based innovation, potential adopters, practice environment, implementation process, and adoption outcomes.DiscussionThe findings are expected to inform future research and support the integration of sleep disorder screening into stroke care pathways. Ultimately, the review will improve stroke outcomes by addressing sleep health as a critical but often overlooked component of post-stroke management.Scoping review registrationOpen science framework (osf.io/tb7z8).